Catalysts of self-assembled Pt@CeO2−δ-rich core-shell nanoparticles on 3D ordered macroporous Ce1−xZrxO2for soot oxidation: nanostructure-dependent catalytic activity - Wei, Y.; Jiao, J.; Zhang, X.; Jin, B.; Zhao, Z.; Xiong, J.; Li, Y.; Liu, Jian; Li, J. (R S C Publications, 2017)
© The Royal Society of Chemistry. The catalytic performance in heterogeneous catalytic reactions consisting of solid reactants is strongly dependent on the nanostructure of the catalysts. Metal-oxides core-shell (MOCS) nanostructures have potential to enhance the catalytic activity for soot oxidation reactions as a result of optimizing the density of active sites located at the metal-oxide interface. Here, we report a facile strategy for fabricating nanocatalysts with self-assembled Pt@CeO 2−δ -rich core-shell nanoparticles (NPs) supported on three-dimensionally ordered macroporous (3DOM) Ce 1−x Zr x O 2 via the in situ colloidal crystal template (CCT) method. The nanostructure-dependent activity of the catalysts for soot oxidation were investigated by means of SEM, TEM, H 2 -TPR, XPS, O 2 -isothermal chemisorption, soot-TPO and so on. A CeO 2−δ -rich shell on a Pt core is preferentially separated from Ce 1−x Zr x O 2 precursors and could self-assemble to form MOCS nanostructures. 3DOM structures can enhance the contact efficiency between catalysts and solid reactants (soot). Pt@CeO 2−δ -rich core-shell nanostructures can optimize the density of oxygen vacancies (O v ) as active sites located at the interface of Pt-Ce 1−x Zr x O 2 . Remarkably, 3DOM Pt@CeO 2−δ -rich/Ce 1−x Zr x O 2 catalysts show super catalytic performance and strongly nanostructure-dependent activity for soot oxidation in the absence of NO and NO 2 . For example, the T 50 of the 3DOM Pt@CeO 2−δ -rich/Ce 0.8 Zr 0.2 O 2 catalyst is lowered down to 408 °C, and the reaction rate of the 3DOM Pt@CeO 2−δ -rich/Ce 0.2 Zr 0.8 O 2 catalyst (0.12 μmol g −1 s −1 ) at 300 °C is 4 times that of the 3DOM Pt/Ce 0.2 Zr 0.8 O 2 catalyst (0.03 μmol g −1 s −1 ). The structures of 3DOM Ce 1−x Zr x O 2 -supported Pt@CeO 2−δ -rich core-shell NPs are decent systems for deep oxidation of solid reactants or macromolecules, and this facile technique for synthesizing catalysts has potential to be applied to other element compositions.